2021
DOI: 10.3390/socsci10090349
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Trust in Public Authorities Nine Months after the COVID-19 Outbreak: A Cross-National Study

Abstract: This study aimed to examine the perceived trust in information provided by public authorities and financial measures put in place to address the impact of COVID-19. Using a cross-national approach among four Western countries—the United States of America, Norway, Australia, and the United Kingdom—provides an analysis of responses related to trust and how they were associated with age group, gender, education level, employment status, size of place of residence, infection status, and social media use. When cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Although vaccination has been identified as an effective measure of reducing the spread of COVID-19, 65% of respondents in a survey in the UK reported that they would not voluntarily engage in a vaccination process (O'Callaghan 2020). Lack of trust in the government, concerns of side effects, time taken to develop and test the vaccine, and belief of limited inclusion of diverse populations in studies can impact the public perception of obtaining the vaccine when determined to be available to the public (Price et al 2021;Ballantyne and Ganguli-Mitra 2021;O'Callaghan 2020;Moon 2020;Latkin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although vaccination has been identified as an effective measure of reducing the spread of COVID-19, 65% of respondents in a survey in the UK reported that they would not voluntarily engage in a vaccination process (O'Callaghan 2020). Lack of trust in the government, concerns of side effects, time taken to develop and test the vaccine, and belief of limited inclusion of diverse populations in studies can impact the public perception of obtaining the vaccine when determined to be available to the public (Price et al 2021;Ballantyne and Ganguli-Mitra 2021;O'Callaghan 2020;Moon 2020;Latkin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Social demographics, attitudes, beliefs, and social norms can influence a person's willingness to obtain a vaccine (Bennett et al 2011;Zimmerman et al 2003;Price et al 2021). The Theory of Planned Behavior suggests that attitudes and beliefs influence intention (e.g., the intention to take the vaccine), which in turn is a strong predictor of specific health behaviors (actually taking the vaccine) (Ajzen 2002;Hagger et al 2016;Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sheer volume of information and conflicting messages was challenging for individuals having to interpret and understand this information in order to form their own views, opinions and to inform their responses to the first pandemic to occur in a century [10,18]. The high and frequent use of social media over the course of the pandemic has been identified as having a negative impact on mental health, wellbeing, and loneliness [19,20]. Whilst social media allowed news to be spread fast, it was also compromised by the lack of governance and misinformation shared based on personal opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Social Media Guidance and signposting to credible sources of information would have been useful for social media users. Additionally, educational institutions could have responded to this by providing informative support in spotting credible sources of information and differentiating from 'fake news' [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a global survey from 57 countries found that media freedom reduced political trust overall, but trust levels varied with people's education ( Rieger and Wang, 2021 ). Another study based on data from the U.S., Norway, Australia, and the U.K. investigated whether social demographic factors such as age, gender, education, employment, place of residence, and social media usage influenced political trust during Covid-19 ( Price et al, 2021 ). However, another global study with respondents from 178 countries revealed different results ( Gozgor, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%